Achievement of high efficiency with extremely low efficiency roll-off in solution-processed thermally activated delayed fluorescence OLEDs manufactured using xanthone-based bipolar host materials. Issue 20 (22nd April 2020) - Kim, Chae Yeong; Lee, Chiho; Kim, Hyung Jong; Hwang, Jinhyo; Godumala, Mallesham; Jeong, Ji-Eun; Woo, Han Young; Cho, Min Ju; Park, Sungnam; Choi, Dong Hoon
Abstract : Two bipolar hosts as structural isomers were designed and synthesized for solution-processable green TADF-OLEDs. Corresponding devices showed excellent EQE over 21% and low efficiency roll-off. Abstract : The use of soluble host materials and thermally activated delayed fluorescence (TADF) emitters is indispensable for developing high-efficiency organic light-emitting diodes (OLEDs) by cost-effective solution processes. In this study, two bipolar hosts were designed as structural isomers, namely 3-(3, 5-di(9 H -carbazol-9-yl)phenyl)-9 H -xanthen-9-one (Xp-mCP ) and 2-(3, 5-di(9 H -carbazol-9-yl)phenyl)-9 H -xanthen-9-one (Xm-mCP ). The two host materials were synthesized by combining the unipolar host, 1, 3-di(9 H -carbazol-9-yl)benzene (mCP) with 9 H -xanthen-9-one as an electron-accepting moiety. The two hosts exhibit good solubility in various organic solvents and high triplet energy ( E T = 2.67 eV for Xp-mCP and E T = 2.82 eV for Xm-mCP ), which renders them suitable for t4CzIPN-containing solution-processable green TADF-OLEDs. The maximum external quantum efficiency (EQE) values were 19.3% and 22.0% for Xp-mCP - and Xm-mCP -based green TADF-OLED, respectively. Among them, the device comprising Xm-mCP showed an excellent efficiency roll-off behavior by displaying only a 4.5% decrease and 11.4% decrease at 1000 cd m −2 and 2000 cd m −2, respectively. These results show the significant potential of xanthone-mCP host materials to develop solution-processable OLED technologies.